LEKSIKAL TAKSONOMI MAKANAN DALAM BAHASA INGGRIS DAN BAHASA SUNDA (SUATU ANALISIS KONTRASTIF) - KRISTINE OLIVIA SONDAKH, GITA KRISTINE OLIVIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research is entitled â€œLexical Taxonomy of Food in English and Sundanese (A Contrastive Analysis)â€. The objectives of this research are to identify, classify and describe the lexical taxonomy of food and to analyze the similarities and differences of food taxonomy used in both languages. This research uses a descriptive method. There are three steps to finish this research, the first step is preparation. In this step, the writer reads some books about lexical taxonomy. The second step is data collection. In this step, the writer collets the kinds of food that include in lexical taxonomy in English and Sundanese. The third step is data analysis. In this step, the writer identifies, classifies, and describes the data about lexical taxonomy in English and Sundanese according to Frisch in Hickerson (1980:120) theory and then the writer uses Ladoâ€™s (1957:114) theory to contrast the data of both languages. The results show that in solid and liquid foods, there are several types of food, such as: rice, fruits, vegetables, bread, meat, fish/seafood, processed food, alcoholic beverages and non-alcoholic beverages. The second results show that the lexical taxonomy of food has variation. For example, in English, the variety of food is bread and in Sundanese the variety of food is rice, because bread and rice are the main food. Whereas, the lack variety of food is tuak, because it only has one kind of alcoholic drink. The findings of this research support the theory of Frisch in Hickerson and Lado. Keywords: Lexical Taxonomy of Food, English and Sundanese, Frisch in Hickerson, Lado.